Biological potential of an ethanolic extract from "Mela Rosa Marchigiana" pulp callus culture. (December 2020) - Potenza, Lucia; Minutelli, Mattia; Stocchi, Vilberto; Fraternale, Daniele
Graphical abstract: Highlights: The ethanolic extract from Mela Rosa Marchigiana pulp callus contains triterpenes. The biological effects of the ethanolic extract were investigated. Cell-free and cell-based models were used. Cell-free models showed antioxidant and genoprotective activities. Cell models showed positive effect on inflammation, mitochondrial biogenesis and wound. Abstract: The biological effects of the ethanolic extract from Mela Rosa Marchigiana pulp callus were investigated. In terms of the antioxidant activity, the extract exhibited free radical scavenging activity of 67% and 39% using the DPPH assay and ABTS assay respectively. Furthermore, it reduced the ROS production in the keratinocyte cell model of H2 O2 induced oxidative stress. The genoprotective effect was evaluated using the DNA nicking assay, which revealed significant protection up to 70%. The anti-inflammatory response was detected at 0.5 mg/ml through the release of nitric oxide using bacterial LPS and RAW 264.7 cells. Finally, preliminary studies on keratinocytes suggested a possible positive effect of the extract on mitochondrial biogenesis and wound healing. The obtained results encourage further studies to deep the biological effects of this callus with the future objective to propose a product for nutraceutical, cosmetic and food-tech industries, as well as an alternative to normal ways of chemical synthesis.